Acute Posttraumatic Paraplegia Caused by Epidural Hematoma at the Vertex - Messori, Anna; Pauri, Fausto; Rychlicki, Franco; Veronesi, Vanni; Salvolini, Ugo (American Journal of Neuroradiology, 2001)
Summary: Vertex epidural hematomas (VEDHs) are well known but uncommon. Their clinical presentation may be misleading and missed by routine CT axial scanning; thus, diagnosis may be delayed, with possibly fatal consequences. We report a case of acute posttraumatic paraplegia caused by a VEDH, which was evident at CT and for which the patient underwent successful surgery.